Reward frustration and withdrawal from work in health care—a cross-sectional study among health professionals - Hämmig, Oliver (Frontiers in Health Services, 2025)
IntroductionThe health-related consequences of work stress are as broadly studied in the health care sector as they are elsewhere. However, behaviors such as underperforming at work, being less engaged at work, being habitually absent from work without good reason, intending to take unpaid leave, changing jobs or leaving the profession as consequences or correlates of stress and reward frustration at work are largely underresearched, particularly in Switzerland and in health care and across different health professions.MethodsCross-sectional survey data collected from the workforces of six public hospitals and rehabilitation clinics in German-speaking Switzerland were used for this observational study. A total of 1,441 health care workers from various professions participated in the survey. The study focused on effort–reward imbalance (ERI) as a work stress measure and on six different withdrawal behaviors. Relative frequencies stratified by health professions for all study variables (exposure, confounders, and outcomes) and multiple-adjusted odds ratios as measures of association were calculated.ResultsThe findings revealed frequent work stress or rather widespread ERI among health professionals (49%). The results further revealed strong to very strong dose-response relationships between work stress levels and the chance or risk of withdrawal from work. Compared with the least stressed individuals, the most stressed individuals were at significantly increased risk for reduced job performance (aOR = 5.2), low work engagement (aOR = 4.4), increased work absenteeism (aOR = 2.2), and intentions to take unpaid leave (aOR = 3.1), to change the job (aOR = 35.0) or to leave the profession (aOR = 12.3).ConclusionHighly prevalent reward frustration in Swiss health care needs to be reduced to overcome inner resignation and resistance and to prevent health professionals from withdrawing from work, and health care from high follow-up costs above and beyond mere absences from work or high turnover.